Hierarchy and Friendship: Ottoman Practices of Diplomatic Culture and Communication (1290s–1600). (November 2019) - Işıksel, Güneş
Hitherto, no historian has attempted a comprehensive approach to the aims, instruments and practices of Ottoman diplomacy, nor have historians analysed the major claims and evolution of the latter over the longue durée. This article does take a long view, beginning in the 1290s and continuing to the end of territorial expansion, roughly at the turn of the seventeenth century. I propose an exegetic framework to interpret the Ottoman understanding of diplomatic practices, which evolved significantly over the three centuries studied. While changes in the balance of inter-empire power relations were surely a cause, one needs to take account of internal factors as well. As Ottoman sultans and their servitors redefined the political identity of their realm, they redesigned diplomatic practices in conformity with changing priorities.